2002
DOI: 10.1088/0953-8984/14/14/312
|View full text |Cite
|
Sign up to set email alerts
|

EPR study of radiation-induced defects in the thermoluminescence dating medium zircon (ZrSiO4)

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 26 publications
4
39
0
1
Order By: Relevance
“…Extra confirmation of our identification of T1 and T2 as Tb 4+ centres comes from a limited number of literature reports on Tb 4+ in oxide crystals [18][19][20][21][22][23][24]. In these papers, the secondorder ZFS parameters for Tb 4+ centres were found to be typically an order of magnitude larger than those for Gd 3+ centres in the same (or very similar) environments.…”
Section: Tb-related Radiation-induced Centressupporting
confidence: 71%
See 1 more Smart Citation
“…Extra confirmation of our identification of T1 and T2 as Tb 4+ centres comes from a limited number of literature reports on Tb 4+ in oxide crystals [18][19][20][21][22][23][24]. In these papers, the secondorder ZFS parameters for Tb 4+ centres were found to be typically an order of magnitude larger than those for Gd 3+ centres in the same (or very similar) environments.…”
Section: Tb-related Radiation-induced Centressupporting
confidence: 71%
“…In most of the previous observations of Tb 4+ , the four-lines hyperfine splitting ( 159 Tb isotope with I = 3/2, 100 % natural abundance) of the EPR transitions served as ultimate proof for the identification. Resolved hyperfine interaction constants ranging from ~11 MHz in CaWO 4 [18] to ~100 MHz in ZrSiO 4 [22,23] have been reported in these oxide crystals. For the T1 -T3 centres, no such four-lines splitting is observed.…”
Section: Tb-related Radiation-induced Centresmentioning
confidence: 99%
“…Laruhin et al (2002) also demonstrated that lattice defects with thermal instability in SiO m n− groups (e.g., SiO 2 3− defect) easily evanesce even above 120°C and subsequently supply the trapped hole at this thermally instable site into more stable defects such as SiO 2 3− (II). Therefore, the annealing promotes to transfer a part of holes temporarily trapped at thermally instable defect (Laruhin et al, 2002) or impurity such as REEs (Klinger et al, 2012) into the stable lattice defect related to the yellow CL emissions, that is, Frenkel-type defects and SiO m n− groups, resulting in an increase in the yellow emission with a rise in temperature up to 300°C. The Frenkel-type defects and SiO m n− groups may be gradually eliminated from 400 to 600°C and then disappeared above 700°C for 12 hours, which may be responsible for the reduction and absence of the yellow emission bands observed in CL spectra of the MZ sample.…”
Section: Yellow Emission Bandmentioning
confidence: 92%
“…These phenomena concerning yellow PL and IL emissions may be caused by a formation of lattice defect. Based on comparisons of the luminescent properties with ESR data obtained from previous studies (Gaft et al, 2002;Laruhin et al, 2002), Finch et al (2004) assigned the yellow emissions to Frenkel-type defects and SiO m n− groups because a variation of ESR signal patterns are mostly corresponding to those of IL and PL behaviors and these defect centers are relatively thermally-stabile compared with other type of defects formed by radiation. On the other hands, it is known that (UO 2 ) 2+ also acts as an activator in PL and laser-induced luminescence of zircon in yellow spectral region (Gaft et al, 2002;MacRae and Wilson.…”
Section: Yellow Emission Bandmentioning
confidence: 98%
“…Therefore the thermoluminescence (TL) and electron paramagnetic resonance (EPR) caused by some trivalent rareearth (Tb 3+ , Dy 3+ ) ions in zircon was recently studied [8,9]. However few studies on actinide (5f n ) ions in zircon have been performed.…”
Section: Introductionmentioning
confidence: 99%